Athletes` rest-activity circadian rhythm differs in accordance with the sport discipline - Vitale, J. A.; Banfi, G.; Sias, M.; La Torre, A. (Chronobiology International, 2019)
The correct expression of circadian rhythmicity is crucial for the body homeostasis. The rest-activity circadian rhythms (RARs) are involved in the control of the sleep-wake cycle and altered RARs could lead to a compromised health status. Many studies focused on examining sleep behavior and circadian rhythms in physically active subjects or athletes but, unexpectedly, no data on RARs are available. Therefore, we studied the existence of the RAR in athletes and the possible difference in RAR`s characteristics among sport disciplines. The study had a prospective observational design and RARs were recorded for five consecutive training days through actigraphy (Actiwatch 2 actigraph; Philips Respironics, OR, USA) in 43 athletes (mean age: 25.6 ± 3.2 years). Athletes competed in three different disciplines and had different training schedules and competition levels: professional triathletes (N = 10; 6 females and 4 males) had 2 morning (08:30-12:00) and 1 afternoon (15:00-17:00) training sessions, professional volleyball players (N = 19; 12 females and 7 males) used to train once in the morning (09:00-11:30) and once in the afternoon (15:00-18:00), and non-professional soccer players (N = 14; all males) trained always late in the evening (20:30-22:30). To determine the existence of RARs, the activity counts (A.C.) data were analyzed using the single and the population mean cosinor method; a one-way analysis of variance (ANOVA) followed by the Tukey-Kramer post-hoc test was used for the comparison of RAR characteristics among soccer, volleyball and triathlon athletes. Partial eta squared (?p2) was used to determine the magnitude of the effect for significant outcomes (a = 0.05) in ANOVA. The presence of a significant RAR both for each of the 43 athletes (p < 0.001) and for the three categories of athletes (p < 0.001) was observed. RARs differed among sport disciplines: the Midline Estimating Statistic of Rhythm (MESOR) was significantly higher in triathletes (mean: 347 A.C. with 95% Confidence Interval [CI]: 314-379) compared to both volleyball (mean: 188 A.C. with 95% CI: 173-203; p < 0.001) and soccer players (mean: 289 A.C. with 95% CI: 267-312; p < 0.01) with ?p2 = 0.72. Amplitude (A) values showed the same significant trend of MESOR data (ANOVA: p < 0.001; ?p2 = 0.65) while the acrophase (F) occurred at 18:28 for soccer players, significantly later than triathlon (15:20 h; p < 0.001) and volleyball players (16:24 h; p < 0.001) (ANOVA: p < 0.001; ?p2 = 0.84). The higher training duration and intensity reached by triathlon athletes in the morning sessions caused a phase advance of their RAR`s acrophase F and higher MESOR and A amplitude compared to volleyball players and triathletes. Therefore, different sport disciplines require different training schedules, training loads and intensities that translate into different RARs. Strength coaches and medical staff of professional teams should strongly consider actigraphy as a practical and powerful tool to monitor RARs, sleep behavior, and the activity levels of their athletes; highlighting potential circadian disruptions through actigraphy could be helpful to prevent musculoskeletal injuries.